Analisis Persepsi Dan Pengelolaan Taman Nasional Baluran Berbasis Ekowisata - purwanto, sulis (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
Ecotourism is a form of sustainable tourism development that benefits natural, economic and socio-cultural environments. The issue of glombal warming is aware of the importance of developing tourism with the concept of sustainable ecoturism. The aplication of the ecotourism concept can minimize the negative impacts that accur mainly on the natural environment. This article aims to analyze tourist perceptions and tourism development related to ecoturism principles.The data was obtained by observation, questionnaires, in-depth interviews and literature study. Then, the data were analyzed using descriptive frequency qualitative techniques. The result showed that tourist perceptions of the destinasion in Baluran national Park consisted of three variables, namely accessibility, facilities, and attractions. In accessibility variables, tourist perception are not good, facilities anf attractions ara classified as good. Tourism development related to ecotourism that manager have adopted the conscept of ecotourism as stated in the stategic plan in 2015-2019. Implementation of the basic principle of ecotourism according to the international Ecotourism Society in Baluran National Park is quite good by percentage of 73%. Generally , the principle indicators of ecotourism have not been maximally, so there is a need to improve the quality of tourism products, especially ecotourism